Significant production of alkyl halides from (aliphatic) carboxylic acids in the UV/chlorine process - Xueling Bai; Xiaoqing Li; Baoqiang Hao; Renyuan Zhang; Genye He; Zishi An; Bing Zheng; Jing Li (Journal of Hazardous Materials Letters)
Ultraviolet radiation combined with free chlorine (UV/chlorine) is an attractive alternative to UV or chlorination alone for disinfection. However, •OH and Cl• radicals from UV/chlorine have recently raised increasing concerns about the possible formation of chlorinated products. A significant quantity of alkyl halides was generated from aliphatic carboxylic acids in the UV/chlorine process, in contrast to the absence of any detectable alkyl halides during chlorination alone. During the UV/chlorine process, the formation of CH3Cl, CH3CH2Cl and CH3CH2CH2Cl were was observed from acetic acid, propionic acid and n-butyric acid, respectively. The maximum yield of CH3Cl was up to 54.6 % when acetic acid was treated at a chlorine to precursors (Cl/P) ratio of 4.0. In addition to CH3Cl, CH2Cl2 and CHCl3 were also detected as the products of acetic acid. The presence of bromide ions resulted in a reduction in the yields of chloroalkanes, the formation of bromine byproducts, and an increase in the total amount of halocarbons. Hydroxyl radicals and chlorine radicals were identified as key reactants in the radical quenching experiments. The reactions described in this paper contribute to the understanding of the mechanism of halogenated byproduct formation during the UV/chlorine process. Synopsis: The radicals resulting from UV/chlorine lead to the conversion of carboxylic acids into a significant amount of alkyl halides that would not be generated by chlorination alone.